INCOME EQUITY IN THE PERUVIAN PENSION SYSTEM: PERIOD 2012-2022 - Espinoza Rivera, Marco Aurelio (2024)
This study delves into the Peruvian pension system between 2012 and 2022, with a particular emphasis on the equity of retirement pension incomes and the determinants of these inequities. Employing a quantitative approach and the implementation of advanced machine learning techniques, including XGBoost regression models and SHAP analysis, a representative sample of 858,474  pensioners was analyzed. The findings reveal a significant discrepancy between pensioners in the National Pension System and those in the Private Pension System, with the latter's pensions being on average higher. The study identifies key factors in pension income equity as educational level, geographic location (Lima versus other regions), age, gender, and employment sector (public or private). Notably, the educational level of pensioners accounts for almost 20% of the retirement pension amount, highlighting its significant role in determining retirement income. This finding is of particular importance for public policy formulation, suggesting that improving access to education could be a key strategy to enhance equity in the Peruvian pension system.